The effects of titanium dioxide (TiO2) content on the dry sliding behaviour of AA2024 aluminium composite / Hamid M. Mahan ... [et al.] - M. Mahan, Hamid; Konovalov, S.V; Panchenko, Irina; Al-Obaidi, Mudhar A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The low density, low expansion coefficient, and strong corrosion resistance at room temperature of Aluminium alloys have made them a popular choice for engineering applications. In this study, Aluminium AA2024 alloys are prepared with different weight contents of ceramic material, titanium oxide (TiO2) nanoparticles (0%, 2.5%, 5%, and 7.5% wt.) of a particle size of 30 nm using the metal stir casting method. The hardness property and wear resistance with the effect of heat treatment are investigated using a pin-on-disc wear device for both the base alloy and the reinforced alloys. The result shows the prosperity of 5wt.% of TiO2 to attain the optimum hardness and wear resistance. Using the optimum content of TiO2 and heat treatment, the hardness and wear resistance of 5wt.% TiO2-AA2024 nanocomposite has been significantly improved after heat treatment over the unreinforced Aluminium matrix. Statistically, the hardness and wear resistance are improved by 68% and 22%, respectively. This is due to an increased number of fine precipitates besides their uniformly distributed after heat treatment. Furthermore, casting AA2024 Aluminium alloy material mainly has S (Al2CuMg) and Al3TiCu phases. The appearance of a large number of S phases causes a significant improvement in the properties of the alloy.